Directives of Communicability for Software Artifacts - Damian, Adriana Lopes; de Souza, Clarisse Sieckenius; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
Software artifacts created in the early stages of the development process describe the proposed solutions for the system, such as UML and prototypes. For this reason, these artifacts are important for team communication. Miscommunication via artifacts occurs because practitioners typically focus on modeling, without reflecting on how other software development team members interpret them. Incorrect information during the development process can be introduced in the system due to miscommunication, impacting its quality. In this context, this work aimed to answer the following research question: How to support effective communication between producers and consumers of artifacts developed in the early stages of software development? To answer this question, we proposed the Directives of Communicability (DCs), based on theories that investigate different communication perspectives and exploratory studies. We designed the DCs to support practitioners to analyze characteristics that affect the artifact's content on communication. We conducted different empirical studies with our proposal, with 105 participants from industry and academia. From the empirical studies results, we noticed the DCs supported the reflection of producers’ artifacts, contributing to effective communication and reducing defects caused by miscommunication.